City of Staunton, Va. Code Ch. II, § 135 p. 115 (1910) - (:unkn) unknown (General Publisher, 1910)
Prohibited carrying of firearms, throwing stones, or other missiles within the park.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES